2021
DOI: 10.1155/2021/9995614
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinesterase Activity of Eight Medicinal Plant Species: In Vitro and In Silico Studies in the Search for Therapeutic Agents against Alzheimer’s Disease

Abstract: Many Bangladeshi medicinal plants have been used to treat Alzheimer’s disease and other neurodegenerative diseases. In the present study, the anticholinesterase effects of eight selected Bangladeshi medicinal plant species were investigated. Species were selected based on the traditional uses against CNS-related diseases. Extracts were prepared using a gentle cold extraction method. In vitro cholinesterase inhibitory effects were measured by Ellman’s method in 96-well microplates. Blumea lacera (Compositae) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…Surprisingly, significant AChE inhibition activity results was observed in A. calamus mediated HAp NPs, suggesting that the preparation of HAp NPs from A. calamus rhizome extract enhanced the AChE inhibition. Similar observations were made by Uddin et al (2021) where the extracts of Blumea lacera, Cyclea barbata, Smilax guianensis and Byttneria Pilosa inhibited AChE with an IC50 values of 150 ± 11, 176 ± 14, 205 ± 31, and 221 ± 2 μg/ml respectively Uddin et al (2021). They also proved that the plant extracts selected in their study showed a promising effect in inhibiting AChE activity, wherein the present study has shown improvement in biological activities in the medicinal plants when in combination with nanoparticle.…”
Section: Discussionsupporting
confidence: 89%
“…Surprisingly, significant AChE inhibition activity results was observed in A. calamus mediated HAp NPs, suggesting that the preparation of HAp NPs from A. calamus rhizome extract enhanced the AChE inhibition. Similar observations were made by Uddin et al (2021) where the extracts of Blumea lacera, Cyclea barbata, Smilax guianensis and Byttneria Pilosa inhibited AChE with an IC50 values of 150 ± 11, 176 ± 14, 205 ± 31, and 221 ± 2 μg/ml respectively Uddin et al (2021). They also proved that the plant extracts selected in their study showed a promising effect in inhibiting AChE activity, wherein the present study has shown improvement in biological activities in the medicinal plants when in combination with nanoparticle.…”
Section: Discussionsupporting
confidence: 89%
“…In the correlation analysis, eriodictyol and hydroxytrimethoxyflavone II strongly correlated with the observed anti-cholinesterase inhibitory activity ( Figure 5 ). Our results also agree with the data reported by Uddin et al [ 53 ] and Uriarte-Pueyo and Calvo [ 54 ]. Tyrosinase plays a key role in the synthesis of melanin and is therefore a checkpoint in the treatment of hyperpigmentation [ 55 ].…”
Section: Resultssupporting
confidence: 94%
“…Neuroinflammation, driven by an increase in nitric oxide (NO), interleukin‐6 (IL‐6), interleukin‐1 (IL‐1), TNF‐α, and other cytotoxic chemicals, is another pathogenic mechanism in AD 78 . A deficiency of cholinergic neurons has also been observed in AD, with cholinergic deficiency linked to the cognitive impairment seen in AD due to the degeneration of cholinergic neurons in the basal forebrain 82 …”
Section: The Specific Impact Of Kaempferol On Neurological Diseasesmentioning
confidence: 99%